EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA SALATIGA - Pramestya, Olivia Sheva; Graciafernandy, Maria Augustine (Fakultas Ekonomi, Universitas Semarang, 2023)
One of the efforts made by the Salatiga City Government to increase revenue from Regional Original Revenue is through hotel and restaurant taxes. This research was conducted at the Salatiga Regional Revenue and Financial Management Agency. The purpose of this study was to determine the level of effectiveness and contribution of hotel and restaurant taxes to Local Revenue in the City of Salatiga. This study uses a quantitative descriptive method using secondary data obtained from the Salatiga Regional Revenue and Financial Management Agency, which consists of reports on targets and realization of hotel and restaurant taxes as well as Salatiga City regional revenue. The data is processed using the effectiveness ratio and contribution ratio. The overall results of the research show that in 2017-2021 the effectiveness of hotel and restaurant taxes is classified as a very effective criterion for local revenue. Meanwhile, the contribution value of hotel and restaurant taxes is still very low in terms of local revenue.